Thermodynamic evaluation of pure Co for the third generation of thermodynamic databases. Issue 2 (30th September 2016) - Li, Zhou; Bigdeli, Sedigheh; Mao, Huahai; Chen, Qing; Selleby, Malin
Abstract : An updated thermodynamic description of pure Co was obtained by applying new models for the third generation of Calphad databases. In these models, different contributions to the heat capacity, especially the vibrational part, were treated separately, each with a clear physical meaning. More importantly, the phase stabilities of the various allotropes are now physically well defined. Thus, the derived thermodynamic properties vary more reasonably and smoothly from 0 K and up. Calculated thermodynamic properties were compared with experimental data and good agreement was obtained.